The impact of the biology images interpretation on the quality of the critical thinking development - Villamar Vera, Isaac; Castro Jaime, Maria Alexandra; Herrera Moscol, Maria Gabriela (Revista Minerva, 2023)
In this 21st century, it is necessary for the individual to quickly adapt to the changes that occur in their environment and have a better understanding of natural phenomena. Therefore, one of the most important cognitive processes in this century is critical thinking, which must be taught in key subjects where the student can discern the information they receive, and one of these subjects is biology. For the development of this method, it is necessary to include new tools that help in the understanding of the topics to be discussed in class, including the use of images. For this reason, this study presents the impact generated by the use of visual material in the development of critical thinking in subjects such as biology through an experiment in a school course, showing that the use of visual material significantly improves retention capacity and problem analysis.
Keywords: Biology; Critical Thinking; Cognitive Process; Image